Analisa Prefensi terhadap Pemakaian Uang Elektronik Dalam Transaksi pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam UIN Raden Fatah Palembang - Dina Qonita A.R; Sisil Lindia Putri; Andini Herawaty; M Dias Akhira Ramadan; Maya Panorama (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
Electronic money (e-money) is one of the modern means of payment that is currently often used by the public. Many things make people use electronic money as a means of payment to meet their needs and desires, the benefits derived from using electronic money and the influence of the environment are some of the factors that influence interest in using electronic money. The purpose of this study was to find the effect of using e-money on consumptive behavior and to find an increasing consumptive behavior in the use of e-money in students of the Islamic economics and business faculty of Raden Fatah University, Palembang. Analysis of the data used in this study is using primary data obtained from questionnaires from students at the Fakultas Ekonomi dan Bisnis Islam Uin Raden Fatah Palembang.The results of data analysis in this study indicate that the level of understanding of electronic money has a positive effect on student interest in the Faculty of Economics and Islamic Business, Raden Fatah Islamic University, Palembang to use electronic money (e-money). Benefits of using electronic money (e-money).